Unbleached Ethanolamine Empty Fruit Bunch (Efb) Pulp As Partial Substitution For Production Of Autoclave Fibre Cement Composite - Yam, Kok Peng (2019)
The major raw materials for AFCC are cellulose pulp, Ordinary Portland cement and grinded silica; mixed into slurry of 10% solid content and mostly produced using a Hatschek machine. The increasing price of Radiata Pine pulp (up to USD700/ton in year 2015) has force the fibre cement manufacturer to look for alternative pulp source. EFB fibre is readily available in Malaysia and cheaper. The unbleached Ethanolamine pulping process was selected in the study for EFB fibre due to higher ability to retain silica content on EFB pulp surface. Radiata Pine Pulp had superior quality in terms of fibre length, coarseness, fineness, fibre width, wet and dry zero span. However, in terms of fibre count and macro fibrillation index, EFB fibre showed better results. From x-ray diffraction study, silica element was detected on EFB pulp. Recipes with 0 – 13% Radiata Pine pulp content and Cement to silica (C/S) ratio at 0.2, 0.4, 0.6, 0.8 and 1.0 were analyzed. The highest modulus of rupture (MOR) was achieved at 15.5MPa using 9% pulp and 1.0 of C/S ratio. In addition, with the increment of pulp content, impact toughness and deflection of the composites were improved. Subsequent press sheet recipes with interval of 1% EFB pulp content to replace the Radiata Pine pulp at 9% with C/S ratio at 1.0. The results showed that the highest MOR values for both dry (16.7MPa) and wet (9.9MPa) condition were obtained for blended fibre between 6 % Radiata Pine pulp with 3 % EFB pulp. The XRD results showed that silica detected on EFB pulp and formed a flake layer of crystal on EFB pulp surface after autoclaving process. Thus, EFB pulp is suitable as partial substitution for AFCC.